Free radicals and vitamin antioxidants in health and lung diseases - Gautam, Narayan (Journal of Universal College of Medical Sciences, 2015)
Several lung diseases have undergone oxidative stress due to free radical insult. Consequently, antioxidant vitamin C and vitamin E play important role in defense against cellular injury by scavenging free radicals. This article reviews the potential mechanism of free radicals generation and vitamin antioxidant defense to link amongst various lung diseases. One of the manifestations of free radical mediated process is lipid peroxidation subsequently producing malondialdehyde (MDA) in these patients. Supplementation of vitamin C and vitamin E as an adjuvant therapy as well as high intake of fresh fruits and vegetables appear to have a beneficial effect on lung health. Moreover, their consumption should be recommended on a daily basis. Further studies are needed to assess the impact of antioxidants as an adjuvant therapy in patients with lung diseases.